Perioperative Fracture Risk and Two-Year Survivorship of a Short Tapered Femoral Stem following Direct Anterior Approach Cementless Total Hip Arthroplasty with a Fracture Table - Andrews, Samantha; Harbison, Gregory J.; Hasegawa, Ian; Unebasami, Emily; Nakasone, Cass (The Journal of Hip Surgery, 2020)
The cementless, tapered wedge, short femoral stem implant is commonly used in direct anterior approach (DAA) total hip arthroplasty (THA). The lack of access and visualization, however, may increase the risk of perioperative fracture and early failure. Therefore, the current study examined perioperative complications and 2-year implant survivorship following DAA THA performed using a fracture table and short, tapered wedge femoral stem. A retrospective analysis was conducted on patients having undergone DAA THA with a cementless, tapered wedge, short femoral stem. Perioperative fractures were noted and survivorship was determined by the incidence of revision surgery within a minimum 2-year follow-up period. A total 366 consecutive patients (441 hips) were identified in the cohort. Four patients (6 hips; 1.4%) were lost to follow-up and three patients died from unrelated causes. Average follow-up time for the remaining 359 patients (435 hips) was 32.9 ± 10.2 months. There were no intraoperative factures but three perioperative fractures within two weeks. Aseptic loosening occurred in one stem at 13 months, resulting in a 99.1% survival rate with a mean survival time of 23.8 ± 0.1 months (95% confidence interval: 23.6–24.0 months). The use of a short, tapered wedge femoral stem and a fracture table for DAA THA resulted in 0.7% periprosthetic fractures and only one aseptic loosening within 2 years. These results suggest that proper femoral exposure with the use of a fracture table and a short, tapered wedge femoral stem does not appear to increase the risk of periprosthetic femoral fracture.
Keywords: survivorship; total hip arthroplasty; direct anterior approach; short stem; tapered wedge stem; fracture table